Mn-Zn Ferrite Nanoparticles With Silica and Titania Coatings: Synthesis, Transverse Relaxivity, and Cytotoxicity - Kaman, Ondrej; Kulickova, Jarmila; Marysko, Miroslav; Veverka, Pavel; Herynek, Vit; Havelek, Radim; Královec, Karel; Kubaniova, Denisa; Kohout, Jaroslav; Dvorak, Petr; Jirak, Zdenek (IEEE (Institute of Electrical and Electronics Engineers), 2017)
Mn-Zn ferrite nanoparticles of composition Mn0.61Zn0.42Fe1.97O4 and mean size of crystallites d(XRD) = 11 nm are synthesized under hydrothermal conditions as a single-phase product. Subsequently, two coated samples are prepared by encapsulation of the ferrite particles into silica and titania. Transmission electron microscopy confirms the core-shell structure of the products and shows that the cores are actually formed by small clusters of ferrite crystallites. Powder X-ray diffraction, combined with experimental hydrothermal treatment of the titania-coated product, demonstrates that the titania coating is amorphous but can easily be transformed into anatase. The colloidal stability of nanoparticles in water is evidenced by dynamic light scattering, and the respective hydrodynamic sizes are d(Z) = 87 and 157 nm for the silica-coated and titania-coated particles. The colloidal behavior is confirmed based on the measurements of zeta potential, whose negative values lead to strong Coulombic repulsion among coated particles. Magnetic measurements on bare and coated particles show high magnetization of Mn0.61Zn0.42Fe1.97O4 cores and superparamagnetic state at room temperature. The relaxometric study on aqueous suspensions in magnetic fields of 0.5 and 11.75 T reveals high transverse relaxivity of the samples and two distinct forms of its temperature dependence, which are analyzed with respect to the role of temperature-dependent parameters, that is, the diffusion of water and the magnetization of ferrite cores. Finally, careful evaluation of cytotoxicity of coated particles is carried out by using two different methods, namely, the determination of viability and proliferation of Jurkat cells and the real-time monitoring of attachment and proliferation of A549 cells. In the studied range of concentrations, the viability and proliferation of suspension cells are not affected, and only negligible effects are detected in the cell index of adherent cells.
Mn-Zn feritové nanočástice obalené silikou a titanem: syntéza, transverzální relaxivita a cytotoxicita
Keywords: Amorphous titania; cytotoxicity; magnetic nanoparticles; Mn-Zn ferrite; silica; transverse relaxivity; Amorfní titan, cytotoxicita, magnetické nanočástice, Mn-Zn ferit, silika, transverzální relaxivita